Poliomyelitis: Vaccine Coverage in Southeastern Brazil (Research, Society and Development, 2022)
Objective: Analyze polio vaccine coverage in southeast Brazil between 2011 and 2020. Methods: This is a retrospective, descriptive and longitudinal study, with a quantitative approach. The population of the study was individuals vaccinated against poliomyelitis in the Southeast region of Brazil, from 2011 to 2020. To carry out the research, the database of the National Immunization Program using the registration of vaccines available in DATASUS, with subsequent descriptive analysis of the variables obtained. Results: Were observed that the state of Rio de Janeiro had the biggest vaccine coverage from all southeastern states in 2011, but also the lowest in 2020. Moreover, we had a decrease in vaccine coverage in all states amongst 2015 and 2016. In terms of applied doses of IPV and OPV, we had a decline in total quantity from 2011 to 2014, resulting from the reduction of OVP use in this period. Additionally, applications of IVP surpassed OVP in 2015, being the main immunobiological until 2020. Besides, São Paulo had the majority of applied doses in all years, being 2011 the biggest. Lastly, all the doses had numerousness in people younger than one year. Conclusions: In conclusion, this study has shown that the immunizations in southeast Brazil have huge variety between states. As a result, each location requires a specific strategic plan due to different problems in vaccine coverage depending on the location. However, more studies on this area are necessary in order to understand deeply the reason for the decrease in vaccine coverage in certain periods.